Temporal sequences and chaos in neural nets - Riedel, Uwe; Kühn, Reimer; Hemmen, Jan L. van (Physical review. A, Atomic, molecular, and optical physics, 1988)
Exact deterministic equations for the evolution of temporal sequences with a delay stabilization and heat-bath dynamics are derived. The temperature may be arbitrary and both parallel and sequential updating are allowed. The equations display limit-cycle oscillations with a broad diversity of waveforms. For exponential delay it is shown how an increase of the transition amplitude leads to local chaos.
Elektronische Reproduktion der Druckausgabe